KOMITMEN ORGANISASIONAL, KOMPENSATION, KEPEMIMPINAN DAN SYARIAH ENGAGEMENT TERHADAP KINERJA PEGAWAI PERBANKAN SYARIAH DI KOTA MAKASSAR - Indira Basalamah (Jurnal Bisnis dan Kewirausahaan, 2019)
Sharia involvement is the attachment of an individual, physical, emotional, and spiritual influence by belief, justice, balance, freedom, and responsibility towards the organization. The object of research is Islamic banking employees located in Makassar City. Through the cluster sampling technique the samples processed in this study were 185 employees spread across 13 sharia banking offices. Data analysis uses technical path analysis with IBM SPSS Statistics 21 and Amos version 21 Software. The results showed that the level of organizational commitment, compensation, leadership and sharia involvement were 1) organizational commitment, compensation, and leadership had a positive and significant effect on sharia engagement and employee engagement, 2) organizational commitment and compensation indirectly had a positive and significant effect on employee performance through sharia engagement, while leadership does not have a significant influence 3) sharia involvement has a positive and significant influence on employee performance